Islamic Arts and the Expression of Theology: Acehnese Traditional House, Its Ornamentation and Figurative Motifs - Saifuddin Dhuhri (Wacana Seni Journal of Arts Discourse, 2018)
As cultural expression, Islamic arts are coloured by the theologies of the different Islamic sects. However, the discussion of the cultural expressions such as living images and their links to theological expressions has received little attention of scholars. With respect to this, two distinctive views on living images have emerged, including the salafist and the traditionalist views. The salafist view tends to reject living images as the expressions of Islamic arts, whereas traditionalists recognise living images as part of Islamic expressions of arts. This article attempts to demonstrate the modes of living images, which are argued as part of Acehnese Islamic arts and are used in the traditional houses of Rumoh Aceh. Based on a semiotic analysis of the images and historical approach to Rumoh Aceh ornamentation, I argue that earlier motifs of Acehnese ornamentation reflect the salafist view that insists on Arabic calligraphic, geometric and flowery motifs. However, during the colonial period and the 20th century, Rumoh Aceh's ornamentation has been greatly influenced by the traditionalist theology arts. This is evidenced by the use of animal images, like buraqs, peacocks, pigeons and ducks. This study is significant in that it can contribute to the understanding of the nature of Acehnese arts and Southeast Asian Muslim cultural heritage.